Microscopic thymoma and myasthenia gravis. Issue 7 (July 1995) - Puglisi, F; Finato, N; Mariuzzi, L; Marchini, C; Floretti, G; Beltrami, C A
Abstract : A rare case of microscopically sized thymoma is described in a 56 year old man suffering from myasthenia gravis. Histological examination of the surgically removed thymus showed the presence of several epithelial thymoma-like islands. As controls, 100 thymuses obtained from consecutive necropsies were sampled: 4% of these cases showed epithelial islands. This case is further proof that "microscopic thymoma" is a true pathological entity and suggests that every thymus removed from myasthenic patients in which there is no macroscopic evidence of thymoma should be examined microscopically on serial sections.